Suction, hydraulic and strength properties of compacted soils - Kizza, Richard (Nanyang Technological University, 2020)
The objective of the study was to evaluate and investigate simple, economical and yet reliable techniques of measuring unsaturated soil properties i.e.suction, hydraulic and strength properties. These aspects were evaluated using dynamically compacted residual soils. Suction measurements with initially dry and initially wet filter paper have revealed that equilibration time is dependent on initial moisture condition of the filter paper and mode of contact. Initially dry filter paper is preferred over initially wet filter paper. Filter paper in contact mode has shorter equilibration time.It is recommended that contact filter paper can reliably measure suctions both in the low and high range while the non-contact is best suited for suctions above 1000 kPa. A hysteresis of 3-5% has been observed in the filter papers.Permeability estimation using a the mini-disk infiltrometer is comparable with measurements from a falling head flexible wall permeameter indicating that the infiltrometer can be relied on to give quick estimates of saturated permeabilities. Lastly, using conventional strength tests such as Brazilian tensile test, unconfined compression test, undrained unconsolidated test and consolidated undrained test, a framework for constant water content shear strength tests has been suggested to obtain the shear strength parameters of unsaturated soils.